2022
DOI: 10.1002/smtd.202200289
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Cell Membrane‐Cloaked Nanoplatforms for Biomedical Applications

Abstract: Biomimetic approaches utilize natural cell membrane-derived nanovesicles to camouflage nanoparticles to circumvent some limitations of nanoscale materials. This emergent cell membrane-coating technology is inspired by naturally occurring intercellular interactions, to efficiently guide nanostructures to the desired locations, thereby increasing both therapeutic efficacy and safety. In addition, the intrinsic biocompatibility of cell membranes allows the crossing of biological barriers and avoids elimination by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(58 citation statements)
references
References 159 publications
(503 reference statements)
1
50
0
Order By: Relevance
“…This suggests that macrophage membrane coating strategy can significantly enhance the targeting and accumulation rate of nanoparticles to the atherosclerotic plaque area. Indeed, the immune evasion ability exhibited by macrophages is essentially a consequence of their surface membrane proteins [ 38 ]. Macrophages can identify MM@Lips-SHP1i NPs as “self-particles” due to the “self-marker” CD47 expressed on the macrophage membrane.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that macrophage membrane coating strategy can significantly enhance the targeting and accumulation rate of nanoparticles to the atherosclerotic plaque area. Indeed, the immune evasion ability exhibited by macrophages is essentially a consequence of their surface membrane proteins [ 38 ]. Macrophages can identify MM@Lips-SHP1i NPs as “self-particles” due to the “self-marker” CD47 expressed on the macrophage membrane.…”
Section: Resultsmentioning
confidence: 99%
“…Nucleusfree cells are substantially easier to isolate and purify, which favours RBC and platelet usage. Extrusion and sonication are common coating methods in laboratory settings with moderate scalability 8 . The former method suffers from high material loss, whereas sonication leads to polydisperse coating, which can translate into unpredictable PK and PD.…”
Section: Manufacturingmentioning
confidence: 99%
“…Due to the complexity of the blood‐brain barrier (BBB), which hinders the delivery of PD‐1 antibodies to tumor sites and further reduces the efficacy. It has been reported that macrophages can cross the BBB and target tumor tissue 91 . PD‐1‐MM@PLGA/RAPAs could not only reduce damage to the central nervous system across the BBB, but also combine ICB and CT to obtain the greatest antiglial in vivo compared to other groups.…”
Section: Biological Functionsmentioning
confidence: 99%